2000
DOI: 10.4319/lo.2000.45.7.1558
|View full text |Cite
|
Sign up to set email alerts
|

Diel changes in phagotrophy by Cryptomonas in Lake Biwa

Abstract: Diel changes in bacterial ingestion by a mixotrophic flagellate, Cryptomonas sp., and heterotrophic nanoflagellates (HNF) were examined in situ at 4-h intervals for 2 d in the epilimnion and metalimnion of Lake Biwa using bacteria-sized fluorescent microspheres as a tracer food. Clearance rates of HNF for the microspheres ranged between 1.3 and 4.5 nl cell Ϫ1 h Ϫ1 , but the average rate did not differ between day and night. In contrast, clear diel changes were observed in the clearance rate of Cryptomonas sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 25 publications
7
53
2
Order By: Relevance
“…The negative correlation between cryptophytes grazing rates and nutrient concentrations is in accordance with the conclusions achieved by Urabe et al (2000) in Lake Biwa, which claimed that cryptophytes use phagotrophy as an alternative source of nutrients. Interestingly, CR and CSGR of cryptophytes in our experiments were also highly positively correlated with estimators of the in situ light condition: Secchi depth and photoperiod (defined as the number of hours of sunlight per day).…”
Section: Factors Controlling Ingestion Rates In the Dominant Mixotrophssupporting
confidence: 78%
See 1 more Smart Citation
“…The negative correlation between cryptophytes grazing rates and nutrient concentrations is in accordance with the conclusions achieved by Urabe et al (2000) in Lake Biwa, which claimed that cryptophytes use phagotrophy as an alternative source of nutrients. Interestingly, CR and CSGR of cryptophytes in our experiments were also highly positively correlated with estimators of the in situ light condition: Secchi depth and photoperiod (defined as the number of hours of sunlight per day).…”
Section: Factors Controlling Ingestion Rates In the Dominant Mixotrophssupporting
confidence: 78%
“…Then, the time elapsed from sampling and the start of the experiment, would have probably been too short to allow the cells to adapt to the in vitro light conditions. Urabe et al (2000) and På lsson and Grané li (2003) observed that different species of freshwater Cryptomonas exhibited significant diurnal differences in bacterial ingestion rates, with the lowest values recorded during the night. These results suggest that phagotrophy in these organisms would be light dependent and that they might not survive using bacterivory as the unique mode of nutrition.…”
Section: Factors Controlling Ingestion Rates In the Dominant Mixotrophsmentioning
confidence: 99%
“…The dominance of Cryptophyceae on different sampling dates, can be explained by the fact that Cryptomonas marsonii and C. cf. obovata (Y FG), are typical mixotrophic flagellated organisms that can withstand occasional nitrogen and light limitation, as they can ingest bacteria (Tranvik et al, 1989;Jones, 2000;Urabe et al, 2000;Sinistro et al, 2007;Unrein et al, 2007;Allende et al, 2009). This fact, and the capacity to migrate vertically in order to reach optimum light condition, allowed them to remain in the water column during the whole phytoplankton succession, and to reach a greater contribution when macrophyte cover was more profuse and/or DIN concentration was low in the late re-flooding period.…”
Section: Discussionmentioning
confidence: 99%
“…(Cryptophyte) and Dinobryon spp. (Chrysophyte), have been show to exhibit significant diurnal differences in bacterial ingestion rates, with the highest rates measured in late afternoon (Urabe et al 2000;På lsson and Granéli 2003). Experimental evidences obtained in vitro with cultures of mixotrophic chrysophytes (Dinobryon cylindricum) and haptophytes (Chrysocromulina ericina) have also demonstrated that higher biomass, cell density, or growth rates are usually achieved in light conditions as compared to darkness (Caron et al 1993;Hansen and Hjorth 2002).…”
Section: Relative Grazing Effect Of the Different Flagellate Types-mentioning
confidence: 99%
“…Mixotrophy, defined here as the combination of photosynthesis and particle grazing (sensu Sanders 1991), has been observed in most phytoflagellated groups: chrysophytes (Bird and Kalff 1986), dinoflagellates (Stoecker et al 1997), cryptophytes (Urabe et al 2000), dictyochophytes (Nygaard and Tobiesen 1993), euglenophytes (Epstein and Shiaris 1992), and haptophytes (Skovgaard et al 2003). Although the ability to ingest particulate material by unicellular algae had been described almost one century ago (Biecheler 1936), the potential significance of this behavior for the elemental flow through the microbial food web was recognized only during the last two decades (Sanders 1991).…”
mentioning
confidence: 99%